Exploring the Nexus Between a Supportive Workplace Environment, Employee Engagement, and Employee Performance in the Kingdom of Saudi Arabia - Samma Faiz Rasool; Hana Mohelska; Fazal Ur Rehman; Hamid Raza; Muhammad Zaheer Asghar (Administrative Sciences, 2025)
Grounded in motivation theory, this study examines the direct relationship between a supportive workplace environment (SWE) and employee performance (EP). The SWE has been identified into three dimensions, i.e., work recognition (WR), work motivation (WM), and career development (CD). Moreover, we focused on the mediating effect of employee engagement (EE) on the relationship between SWE and EP. A quantitative research method was used, and data were collected through a questionnaire survey. Data were collected from 349 respondents. The target population were the senior managers, middle managers, and administrative staff working in the semi-government organizations based in Riyadh, Saudi Arabia. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) software version 4.0. The results indicate that in the direct relationship, workplace recognition, workplace motivation, and career development are positively connected with EP. Similarly, the findings show that employee engagement positively mediates between an SWE (work recognition, work motivation, and career development) and EP. This study suggests that managers can establish practices acknowledging and appreciating employee contributions, leading to increased motivation and improved performance. Creating a work environment that fosters work motivation by addressing employees’ physical and safety, social, and egoistic needs can further enhance employee engagement and performance. The study highlights the significant role of work recognition, work motivation, career development, and employee engagement in influencing employee performance. This study also recommends some practical implications for the semi-governmental organizations. First, it was suggested that organizations create a workplace environment in which employees feel appreciated, valued, and happy. Second, the organizations introduce the employee engagement culture at the department level as well as at the organizational level. Third, the organizations also introduce flexible work schedules for middle-level and administrative staff. Finally, Saudi organizations recognize the output of their employees and provide them with monetary incentives.